Acquired sperm hypomethylation by gestational arsenic exposure is re-established in both the paternal and maternal genomes of post-epigenetic reprogramming embryos - Keiko Nohara; Takehiro Suzuki; Kazuyuki Okamura; Tomoko Kawai; Kazuhiko Nakabayashi (Epigenetics & Chromatin)
Abstract Background DNA methylation plays a crucial role in mammalian development. While methylome changes acquired in the parental genomes are believed to be erased by epigenetic reprogramming, accumulating evidence suggests that methylome changes in sperm caused by environmental factors are involved in the disease phenotypes of the offspring. These findings imply that acquired sperm methylome changes are transferred to the embryo after epigenetic reprogramming. However, our understanding of this process remains incomplete. Our previous study showed that arsenic exposure of F0 pregnant mice paternally increased tumor incidence in F2 offspring. The sperm methylome of arsenic-exposed F1 males exhibited characteristic features, including enrichment of hypomethylated cytosines at the promoters of retrotransposons LINEs and LTRs. Hypomethylation of retrotransposons is potentially detrimental. Determining whether these hypomethylation changes in sperm are transferred to the embryo is important in confirming the molecular pathway of intergenerational transmission of paternal effects of arsenic exposure. Results We investigated the methylome of F2 male embryos after epigenetic reprogramming by reduced representation bisulfite sequencing (RRBS) and allele-specific analysis. To do so, embryos were obtained by crossing control or gestationally arsenic-exposed F1 males (C3H/HeN strain) with control females (C57BL/6 strain). The results revealed that the methylome of F2 embryos in the arsenic group was globally hypomethylated and enriched for hypomethylated cytosines in certain genomic regions, including LTR and LINE, as observed in F1 sperm of the arsenic group. Unexpectedly, the characteristic methylome features were detected not only in the paternal genome but also in the maternal genome of embryos. Furthermore, these methylation changes were found to rarely occur at the same positions between F1 sperm and F2 embryos. Conclusions The results of this study revealed that the characteristics of arsenic-induced methylome changes in F1 sperm are reproduced in both the paternal and maternal genomes of post-epigenetic reprogramming embryos. Furthermore, the results suggest that this re-establishment is achieved in collaboration with other factors that mediate region-specific methylation changes. These results also highlight the possibility that arsenic-induced sperm methylome changes could contribute to the development of disease predisposition in offspring.